Sales Growth Can Moderate The Effect Of Net Income On Dividend Policy - Cusyana, Silvi Reni; Rosid, Abdul; Nurina, Lia; Litamahuputty, Jacomina Vonny; Utami, Sari (Universitas Pahlawan Tuanku Tambusai, 2025)
This study is a quantitative study with an explanatory approach, namely the pednectan which makes previous studies. The data used in this study are secondary data that researchers obtained from the company's annual financial reports from 2015-2025. The data were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that this study aims to analyze Net Profit on Dividend Policy because the P-Values have a positive relationship direction and a significant influence on Dividend Policy because the P-Values are positive and below the significance level of 0.05, namely 0.018. In the next column, the second hypothesis in this study can also be proven. This is because the P-Values are positive and below the significance level of 0.05, namely 0.000. Thus, it can be concluded that the first and second hypotheses in this article can be accepted.